PERBANDINGAN PEMILIHAN PRESIDEN DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA DENGAN KONSEP SYURA DALAM PRINSIP KETATANEGARAAN ISLAM - Muhammad Ihsan; Hasballah Thaib; Faisal Akbar Nasution; Edy Ikhsan (USU LAW JOURNAL, 2016)
ABSTRACTPresidential election process in Indonesia has been reflected in the Constitution of the Republic of Indonesia Year 1945 (1945 Constitution). Since 1945, the presidential election process in Indonesia is consensus in an institution of the People's Consultative Assembly (MPR). It is as the implementation of the Preamble of the 1945 Constitution, all four precepts of Pancasila, "Democracy Led by Wisdom Wisdom In a consultative assembly". Changes in the 1945 Constitution in 1999-2002, has implications in the process of election of the President of deliberation to direct election by the people. Many observers said the process of direct election by the people as a model of democracy. In fact, not a few who claimed the election process by consensus in the Assembly, as well as a model of democracy though indirectly. Implementation of the Presidential election in the concept of Shura as Shura and democracy has no relevance, given some quarters to equate the two. Although there are similarities between shura and democracy as expressed by some. However, there is very substantial between the two, given that it is shura is a method derived from the Rabb al-basyar (Rabb human), namely God, while democracy is the fruit of thinking of a weak man who is certainly not free of shortcomings, democracy sourced of concepts and principles devised by man which the concepts and principles is closely linked to the interests of each individual name in its implementation.Keywords: Presidential Election, Democracy and Shura